Pengaruh Model Pembelajaran Problem Based Instruction Disertai Strategi Guided Note Taking terhadap Hasil Belajar Fisika Siswa Kelas X di SMA Negeri 4 Palu - Fitrah Nur Syafitri; Marungkil Pasaribu; Syamsu Syamsu (Universitas Tadulako, 2021)
This study was conducted with the aim of knowing the effect of the Problem Based Instruction learning model with Guided Note Taking strategy on the physics learning outcomes of class X students at SMAN 4 Palu. This type of research is a quasi-experimental design with a non-equivalent pretest-posttest group design. The population of this study were all students of class X SMAN 4 Palu. The sampling technique used was purposive sampling for class X IPA 3 as the experimental group and class X IPA 7 as the control group. The physics learning outcome instrument is in the form of a multiple choice test that has been validated by an expert validator. The test of physics learning outcomes obtained showed that the posttest average score of the experimental group was 15.10 with a standard deviation of 3.07 and the control group was 12.97 with a standard deviation of 3.10. By using the t-test hypothesis test (two parties), obtained = 2.66 and = 1.67 at the real level = 0.05. This means that the value is outside the reception area. So it can be concluded that there is an effect of the Problem Based Instruction learning model with Guided Note Taking strategy on the physics learning outcomes of class X students at SMAN 4 Palu.